2017
DOI: 10.1007/s10957-017-1102-7
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Paper “The Algebraic Structure of the Arbitrary-Order Cone”

Abstract: In this short paper, we look into a conclusion drawn by Alzalg (J Optim Theory Appl 169:32-49, 2016). We think the conclusion drawn in the paper is incorrect by pointing out three things. First, we provide a counterexample that the proposed inner product does not satisfy bilinearity. Secondly, we offer an argument why a pth-order cone cannot be self-dual under any reasonable inner product structure on R n . Thirdly, even under the assumption that all elements operator commute, the inner product becomes an off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In the same article, it was claimed that L n p is homogeneous, thus showing that it is a symmetric cone under an appropriate inner product. For a discussion of its flaws, we refer to the paper by Miao, Lin, Chen [8]. The result we prove here implies, in particular, that for n ≥ 3 and p = 2, L n p is never a symmetric cone.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In the same article, it was claimed that L n p is homogeneous, thus showing that it is a symmetric cone under an appropriate inner product. For a discussion of its flaws, we refer to the paper by Miao, Lin, Chen [8]. The result we prove here implies, in particular, that for n ≥ 3 and p = 2, L n p is never a symmetric cone.…”
Section: Introductionmentioning
confidence: 73%
“…The authors would like to thank Prof. Chen for kindly agreeing to send us a preliminary version of [8]. The authors would also like to thank an anonymous referee for many valuable suggestions that improved the presentation of this paper.…”
Section: Acknowledgementsmentioning
confidence: 98%
See 1 more Smart Citation
“…Now, although we know that L n+1 p is not homogeneous for p = 2 and n ≥ 2, it still remains to investigate whether L n+1 p could become self-dual under an appropriate inner product. This question was partly discussed by Miao, Lin and Chen in [9], where they showed that a p-cone (again, p = 2, n ≥ 2) is not self-dual under an inner product induced by a diagonal matrix. The results described here show, in particular, that no inner product can make L n+1 p self-dual, for p = 2, n ≥ 2.…”
Section: Introductionmentioning
confidence: 99%